Clinical wastes management in district hospitals of Tumpat, Batu Pahat and Taiping / Prof. Dr. Dasimah Omar, Dr. Subramaniam Karuppannan and Siti Nurshahida Nazli - Omar, Dasimah; Karuppan, Subramaniam Karuppannan; Nazli, Siti Nurshahida (Research Management Institute (RMI), 2013)
The research is a cross-sectional comparative study carried out to determine the variations and similarities in the activities of clinical waste management practices within three district hospitals located in Johor, Perak and Kelantan. Using physical observation, administered questionnaire and interview questions, sectional data within each hospital were collated and analysed by employing Microsoft Excel and relevant statistical analysis tools like ANOVA. The results showed similarities in many areas, confirming that similar activities take place within the hospitals and variations in other areas confirming that many factors both external and internal affect the clinical waste management and other activities within the hospitals. Studies revealed many deficiencies in the management mostly weaknesses in segregation process.